Rabacfosadine for naïve canine intermediate to large cell lymphoma: Efficacy and adverse event profile across three prospective clinical trials. (8th May 2020) - Saba, Corey F.; Clifford, Craig; Burgess, Kristine; Phillips, Brenda; Vail, David; Wright, Zachary; Curran, Katie; Fan, Timothy; Elmslie, Robyn; Post, Gerald; Thamm, Douglas
Abstract: While current lymphoma therapies induce remission in most dogs, drug‐resistant relapse is common, creating a need for novel agents. Rabacfosadine (RAB), a double prodrug of the acyclic nucleotide phosphonate 9‐(2‐phosphonylmethoxyethel) guanine (PMEG), preferentially targets lymphoma cells with reduced systemic toxicity compared with PMEG. Previous studies evaluating RAB administered every 21 days have suggested efficacy in both naïve and relapsed subjects; however, no large studies of RAB as a single agent have been reported in previously untreated dogs with intermediate to large cell lymphoma. The purpose of this study was to evaluate the safety and efficacy of RAB in dogs with previously untreated (excluding corticosteroids) lymphoma. Sixty‐three dogs received up to five RAB treatments every 21 days (16 at 0.82 mg/kg and 47 at 1.0 mg/kg) as a 30 minutes intravenous infusion, with (n = 23) or without (n = 40) concurrent corticosteroids. Response assessment and adverse event (Ae) evaluation were performed every 21 days via Veterinary Cooperative Oncology Group (VCOG) criteria. The overall response rate was 87% (52% CR, 35% PR). The overall median progression free interval was 122 days (199 for CR, 89 for PR and 153 days for all responders). T‐cell immunophenotype and corticosteroid pre‐treatment were predictive of inferior outcomes on multivariate analysis. AEs were most commonly of gastrointestinal origin (hyporexia/diarrhoea) and generally resolved with supportive treatment and/or dosage adjustment. Three dogs experienced VCOG‐CTCAE grade 5 delayed pulmonary fibrosis. In conclusion, RAB administered every 3 weeks is generally well tolerated and demonstrates substantial antitumour activity in dogs with previously untreated intermediate to large cell lymphoma.